Analisis Sistem Pengembangan Desa Wisata Pandean Kabupaten Trenggalek - Muchammad Andika Prasetio; Aditiya Tri Agustian (Faculty of Social and Political Science, 2025)
Pandean Tourism Village, located in Trenggalek Regency, East Java, possesses diverse tourism potential, including natural beauty, local cultural heritage, and promising agricultural resources. This study aims to analyze the development system of Pandean Tourism Village based on Holloway's (2009) 3A theoretical framework, which encompasses three main components of tourism: Attraction, Accessibility, and Amenities. The research employs a descriptive qualitative approach, with data collected through field observation, in-depth interviews with village administrators and community leaders, and documentary studies. The findings indicate that the attraction component in Pandean Tourism Village still requires more optimal management and diversification to compete in the regional tourism market. Accessibility to the tourism village is relatively adequate but requires improvement at several road infrastructure points. Meanwhile, tourism support facilities are still under development and need to be aligned with modern tourist comfort standards. The study concludes that the development of Pandean Tourism Village requires an integrated strategy involving all stakeholders, institutional strengthening, and sustained support from local government policies.